Rare case of intra-oral palatal (soft palate) fibro-lipoma - Mandal, Manit M.; Panchal, Ajay J.; Kumar, Rakesh; Kapadia, Parth B.; Parmar, Neel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Amongst various differential diagnoses possible for intra-oral (palatal) mass, possibility of fibro-lipoma is extremely rare but documented in literature, and hence should be a consideration. Such patient requires thorough evaluation and step-wise approach to treat. This case study documents for a 30-year-old male patient presenting with such mass and chief complaints of post nasal drip, nasal obstruction (right side>left side) and intermittent headache for 3 years. After radiological and endoscopic examination, the mass was surgically removed in toto via dual route (trans-oral and endoscopic). Lipomas are uncommon tumors in the oral cavity, and palate being the rarest amongst them as is our case. It would be strongly advocated to keep lipoma in the differential diagnosis when evaluating a palatal mass. Also, it is worth mentioning and recommending that a careful radiological examination of large lesions arising from the palate is a must before approaching for surgery.